Metafisika Wayang: Dimensi Ontologis Wayang sebagai Simbol Kehidupan - Siswanto, Joko (Jurnal Filsafat "WISDOM", 2003)
This paper attemps to clarify philosophically Wayang as a genetivus objektivus, especially in the western philosophy of view. The investigation finally found out concepts: unification between creation and creator (God), dynamic process of life, proportionality in materiality and spirituality, plurality, and at least life harmony